SUBCLINICAL KIDNEY INJURY IS CAUSED BY A MODERATE SINGLE INFLAMMATORY EVENT. Issue 1 (19th July 2022) - Heinzl, Matthias Wolfgang; Resl, Michael; Klammer, Carmen; Fellinger, Paul; Schinagl, Lukas; Obendorf, Florian; Feldbauer, Roland; Pohlhammer, Johannes; Wagner, Thomas; Egger, Margot; Dieplinger, Benjamin; Clodi, Martin
ABSTRACT: Background: Current means of diagnosis of acute kidney injury (AKI) based on serum creatinine have poor sensitivity and may miss possible therapeutic windows in subclinical kidney injury, especially in septic AKI. Kidney injury molecule-1 (KIM-1) may be a valuable biomarker to improve diagnostic algorithms for AKI. The understanding of septic AKI is still insufficient, and knowledge about KIM-1 kinetics in inflammation is scarce. The aim of this study was to investigate the possible effect of lipopolysaccharide (LPS) on KIM-1 as a marker of structural kidney injury in healthy volunteers. Methods: A single-blinded, placebo-controlled cross-over study using the human endotoxin model (LPS administration) was performed in 10 healthy men. Kidney injury molecule-1 and serum creatinine were measured repetitively for 48 hours. Results: We observed a significant elevation of serum KIM-1 levels after the administration of LPS ( P < 0.001). Furthermore, LPS caused a significant elevation of serum creatinine at an early time point ( P = 0.013) as compared with placebo. Conclusion: Even a relatively small inflammatory stimulus is sufficient to cause subclinical structural kidney injury with elevated KIM-1 and serum creatinine in healthy volunteers. This outlines the insufficiency of the current diagnostic approach regarding AKI and the urgency to develop novel diagnostic algorithms including markers of kidney injury. Clinical Trial Registration: www.clinicaltrials.gov . Unique identifier: NCT03392701 (August 1, 2018)